The HR Unit of the KGB of the Lithuanian SSR: 1954–1991 - Okuličiūtė, Lina (Genocidas ir rezistencija, 2011)
This article describes the structure and operational functions of the HR Unit of the KGB of the Lithuanian SSR, provides an analysis of the ethnic composition of the human resources of the KGB, identifies the peculiarities of training and education of the human resources, and describes the role of part-time employees and the intelligence supplementation reserve.